Control of Spodoptera frugiperda on Fresh Corn via Pesticide Application before Transplanting - Hailiang Han; Bin Chen; Hongxing Xu; Yan Qin; Guiyue Wang; Zhongxian Lv; Xingliang Wang; Fucheng Zhao (Agriculture, 2023)
Background: Pesticide application before transplanting crops has been widely used in rice as an economical and effective method for reducing the use of chemical pesticides. This study focused on the feasibility of the application of pesticides before transplanting in a fresh corn nursery to control Spodoptera frugiperda. Methods: Three pesticides, including 35% Chlorantraniliprole WDG, 6% Spinetoram SC, and 3% Emamectin Benzoate WDG, combined with Polyorganosilicon (HTY-A8) or special flight additives (MF) as synergists were used and their toxicity was determined in the larvae of S. frugiperda feeding on sweet corn in the third leaf stage treated with 5 and 25 times the conventional field application concentration. The best combinations were tested in the field. The results showed that S. frugiperda exhibited high sensitivity to the three pesticides. The period of pest control validity of 35% Chlorantraniliprole WDG and 6% Spinetoram SC in the larvae was about 20 days, while that of 3% Emamectin Benzoate WDG was much shorter. The active component content of Chlorantraniliprole in the corn leaves was significantly higher than that of Emamectin Benzoate and Spinetoram. The pest control effects of Chlorantraniliprole were significantly promoted by HTY-A8 and MF. The field experiment showed that the control effect on S. frugiperda could last for 17 days by spraying Chlorantraniliprole or Spinetoram at 25 times the conventional concentration before transplanting, Furthermore, this method could reduce the amount of active ingredient to 4/5 or 3/4 of that found in a single field spray or seed coating treatment, respectively. Conclusions: This study puts forward a new method to effectively control S. frugiperda in the seedling stage of fresh corn.